Influence of brittle shear damage on accuracy of the two-step method in prediction of structural response to blast loads - Li, Jun; Hao, Hong (Pergamon, 2013)
A two-step numerical approach, which substantially reduces the modelling and computational effort in analysing structural responses to blast loads, was recently proposed. The method solves the responses of the equivalent SDOF system of a structural component during the blast loading phase to obtain the structural displacement and velocity at the end of the blast loading duration. Using these displacements and velocities as initial conditions, a detailed FE model is developed to solve the free-vibration response of the structure. It has been demonstrated that this approach yields very good predictions of structural displacement and longitudinal reinforcement stress at the mid span of RC beams. The accuracy in predicting the stresses in hoop reinforcements near the supports however varies from case to case. One possible reason for this inconsistency in predicting the stresses in hoop reinforcements near the supports is because of the brittle shear damage occurring near the structure supports during the loading phase, which is not considered in the second step free-vibration analysis in the proposed two-step method. To further improve the accuracy of the two-step method, in this paper, the influence of possible brittle shear damage during the blast loading phase is estimated, which will be included in the second step free-vibration analysis to improve the prediction accuracy of the two-step method. Pressure-Impulse diagrams for generic RC beams are generated for straightforward evaluation of the initial damage and the width of the initial damage zone at the end of the blast loading phase for inclusion in the second-step analysis. It is demonstrated that including damage caused by blast loads in the loading phase in the second step free-vibration analysis improves the prediction accuracy of the beam responses to blast loadings.